Diagnosis and treatment of lymphomas in the era of epigenetics. (July 2021) - Chebly, Alain; Chouery, Eliane; Ropio, Joana; Kourie, Hampig Raphael; Beylot-Barry, Marie; Merlio, Jean-Philippe; Tomb, Roland; Chevret, Edith
Abstract: Lymphomas represent a heterogeneous group of cancers characterized by clonal lymphoproliferation. Over the past decades, frequent epigenetic dysregulations have been identified in hematologic malignancies including lymphomas. Many of these impairments occur in genes with established roles and well-known functions in the regulation and maintenance of the epigenome. In hematopoietic cells, these dysfunctions can result in abnormal DNA methylation, erroneous chromatin state and/or altered miRNA expression, affecting many different cellular functions. Nowadays, it is evident that epigenetic dysregulations in lymphoid neoplasms are mainly caused by genetic alterations in genes encoding for enzymes responsible for histone or chromatin modifications. We summarize herein the recent epigenetic modifiers findings in lymphomas. We focus also on the most commonly mutated epigenetic regulators and emphasize on actual epigenetic therapies.